Psychiatric disorders and characteristics of patients in asthmatic children and adolescents (Annals of Medical Research, 2021)
Aim: The main objective of our study is to assess the socioeconomic, prenatal, neonatal and developmental properties of asthma cases who presented to child and adolescent psychiatry clinic and to compare psychiatric diagnosis frequency in terms of age and gender groups.Material and Methods: Patient files of 194 children and adolescents with asthma who admitted to our hospital child and adolescent psychiatry outpatient clinic. were retrospectively reviewed. Patients' age, gender, parent education level and job status, mother's pregnancy history, delivery history, developmental stages and psychiatric diagnoses based on the Diagnostic and Statistical Manual of Mental Disorders- Fifth Edition (DSM-5) are noted. Results: Majority of parents of asthma patients had a primary school education and 21% of mothers were working full time. About 14% of mothers reported smoking during pregnancy and 19% of children had delayed speech. In males and children with primary school age, attention-deficit hyperactivity disorder (ADHD) was frequent whereas female cases showed a higher rate of anxiety disorders.Conclusion: The prevalence of psychiatric disorders, especially ADHD and anxiety disorders, is high in children and adolescents with asthma. The presence of difficulties in terms of sociocultural, prenatal, neonatal and developmental characteristics may increase the need to apply to the psychiatry outpatient clinics.